Decrease of Wine Volatile Aroma Esters by Oxidation - Patrianakou, M.; Roussis, I.G. (South African Journal of Enology and Viticulture, 2013)
The effect of oxidation on the levels of wine volatile aroma esters was studied. Chardonnay wine was bottled either in the presence of nitrogen or air in the headspace. Moreover, Fe II was added to the wine and the bottles were closed in the presence of air. Absorbance values were recorded at 420 nm (browning index), while volatile esters were evaluated during storage using SPME/GC-MS. During wine storage of up to nine months, wines bottled in the presence of air exhibited higher browning indexes and lower levels of several esters, such ethyl acetate, isoamyl acetate, ethyl hexanoate, ethyl octanoate and ethyl decanoate, in comparison to wines bottled under nitrogen. Addition of Fe II led to higher browning indexes and lower levels of several esters during wine storage. In addition, Fe II was added along with H2O2 to Chardonnay wine and the bottles were closed in the presence of air. These additions led to wines with higher browning indexes and lower levels of several esters during wine storage up to 40 days. The present results demonstrate that wine volatile aroma esters can be decreased by oxidation under semi-oxidative and forced oxidative conditions. As a result, oxidation should be taken into account in the decrease of aroma esters during wine storage.